Improving condensing performance of a low-cost floating solar still by surface characteristic alteration. (December 2022) - Lauvandy, Alexander Fernando; Raihananda, Faiz Akbar; Philander, Evan; Luqiyana, Nur Hasyyati; Budiman, Bentang Arief; Fitriyanti, Maya; Juangsa, Firman Bagja; Sambegoro, Poetro
Highlights: Floating solar still performance is increased with the use of anti-fog film. Wettability lower than a surface's critical value is insignificant to transmissivity. Low hysteresis found in the anti-fog film increased the water collection by 33.18% HPC analysis revealed a lower microbial content after the distillation process. Abstract: This work focuses on improving the performance of floating solar still by varying wettability and contact angle hysteresis of the cover surface. Static and dynamic characteristics of droplets on transparent PVC sheet and anti-fog film are measured and applied on a floating solar still prototype. The experimental result shows that wettability is insignificant to transmissivity and absorber temperature since the static contact angles for PVC (44.86°) and anti-fog (13.71°) are below the contact angle critical value (48.63°). However, low contact angle hysteresis found in the anti-fog film promotes the first sliding cycle phenomenon to occur and hence increases the water collection by 33.18%. To assess the quality of the distilled water for domestic use, a heterotrophic plate count (HPC) analysis was also conducted, showing a lower amount of microbial content in the distilled water. These findings can be further considered as a guideline in designing high-performance floating solar still.